2020
DOI: 10.3390/ijerph17124233
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Burden of COVID-19 in Italy: Results of Disability-Adjusted Life Years (DALYs) and Productivity Loss

Abstract: The WHO declared the novel coronavirus disease a pandemic, with severe consequences for health and global economic activity and Italy is one of the hardest hit countries. This study aims to assess the socio-economic burden of COVID-19 pandemic in Italy through the estimation of Disability-Adjusted Life Years (DALYs) and productivity loss. The observational study was based on data from official governmental sources collected since the inception of epidemic until 28 April 2020. DALYs for a disease combines the y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
135
1
15

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(175 citation statements)
references
References 19 publications
10
135
1
15
Order By: Relevance
“…In order to translate DALYs loss pppy into tolerable infection risk, we applied Eqs. (4) , (5) developed by Mara (2008) : where:DALY loss per case of disease is equal to 2.01 × 10 −3 for SARS-CoV-2, as estimated by Nurchis et al (2020) in an observational study based on data from governmental sources obtained since the inception of the epidemic until 28 April 2020; and disease/infection ratio for SARS-CoV-2 is equal to 0.91, as determined in an epidemiological study ( UFPEL – Universidade Federal de Pelotas, 2020a , UFPEL – Universidade Federal de Pelotas, 2020b ) that interviewed and tested 89,397 people for COVID-19 in South Brazil.…”
Section: Methodsmentioning
confidence: 99%
“…In order to translate DALYs loss pppy into tolerable infection risk, we applied Eqs. (4) , (5) developed by Mara (2008) : where:DALY loss per case of disease is equal to 2.01 × 10 −3 for SARS-CoV-2, as estimated by Nurchis et al (2020) in an observational study based on data from governmental sources obtained since the inception of the epidemic until 28 April 2020; and disease/infection ratio for SARS-CoV-2 is equal to 0.91, as determined in an epidemiological study ( UFPEL – Universidade Federal de Pelotas, 2020a , UFPEL – Universidade Federal de Pelotas, 2020b ) that interviewed and tested 89,397 people for COVID-19 in South Brazil.…”
Section: Methodsmentioning
confidence: 99%
“…The world, in a globalized manner, is facing an extraordinary public health emergency in which the nurses are, as always, on the front line. Challenges are even greater in this period of pandemic [ 6 , 7 ], and nurses have the knowledge and aptitudes for providing the care necessary in the different clinical scenarios [ 5 ] that are emerging.…”
Section: Introductionmentioning
confidence: 99%
“…As observed in Malta, a spill off of the viral infection is affecting the elderly population. It has been reported that people beyond 70 years contribute to the highest disability adjusted life years (DALYs) out of the total DALYs if infected by COVID-19 [ 58 ]. This needs to be backed by tailored mitigations and restrictions if and as the need arises, while extensively undergoing rigorous testing, contact tracing covering at least 80% of the COVD-19 positive cases contacts and surveillance of the situation [ 55 ].…”
Section: Resultsmentioning
confidence: 99%